Molecular Recognition of Lipid Antigens by T Cell Receptors - Grant, Ethan P. (The Rockefeller University Press, 1999)
The T cell antigen receptor (TCR) mediates recognition of peptide antigens bound in the groove of major histocompatibility complex (MHC) molecules. This dual recognition is mediated by the complementarity-determining residue (CDR) loops of the α and β chains of a single TCR which contact exposed residues of the peptide antigen and amino acids along the MHC α helices. The recent description of T cells that recognize hydrophobic microbial lipid antigens has challenged immunologists to explain, in molecular terms, the nature of this interaction. Structural studies on the murine CD1d1 molecule revealed an electrostatically neutral putative antigen-binding groove beneath the CD1 α helices. Here, we demonstrate that α/β TCRs, when transferred into TCR-deficient recipient cells, confer specificity for both the foreign lipid antigen and CD1 isoform. Sequence analysis of a panel of CD1-restricted, lipid-specific TCRs reveals the incorporation of template-independent N nucleotides that encode diverse sequences and frequent charged basic residues at the V(D)J junctions. These sequences permit a model for recognition in which the TCR CDR3 loops containing charged residues project between the CD1 α helices, contacting the lipid antigen hydrophilic head moieties as well as adjacent CD1 residues in a manner that explains antigen specificity and CD1 restriction.